Is hysterolaparoscopy a real theranostic approach for anatomical barriers in female fertility? A future argument - Agrawal, Namita; Yadav, Poonam; Fayyaz, S.; Kaur, Brinderjeet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hysterolaparoscopy is a modality that provides the real time abdomino-pelvic view during diagnosis in infertile female patients and any pathology is noticed can be tackled at the same time. So we investigate the theranostic application of hysterolaparoscopy in structural causes of female infertility in present study. Methods: Authors prospectively evaluate 157 female patients (mean age 27.7 years) diagnosed as infertile, underwent hysterolaparoscopy during diagnostic work-up. All the enlisted patients fulfilled the criteria of infertility. The noticed anatomical abnormalities in the hysterolaparoscopy were tackled at the same time if possible. Results: Of the 157 infertile female patients, 93 (~59.2%) were of primary infertility and remaining 64 (~41.8%) were secondary infertility patients. Hysterolaparoscopy showed abnormalities in 125/157 (~85.0%) patients. The detected hysterolaparoscopic abnormalities were distributed in 77/93 (~82.8%) primary and 48/64 (~75.0%) secondary infertility patients. Of the 125 patients with abnormal hysterolaparoscopic findings, 121 (~96.8%) experienced for active therapeutic interventions. All of the 48 secondary infertility patients with hysterolaparoscopic abnormalities experienced for active hysterolaparoscopic interventions. Of 77 patients with hysterolaparoscopic abnormality in primary infertility group, 73 (~94.8%) experienced active intervention. Only four patients with streak ovaries and hypoplastic uterus, few tiny fibroids and adenomyosis did not undergo for active hysterolaparoscopic intervention. Conclusions: Authors concluded that hysterolaparoscopy has a better theranostic approach for the anatomical barriers of female fertility so it can be performed in the initial phases of the infertility diagnostic work-up.